Angiogenesis Induced by Signal Transducer and Activator of Transcription 5A (STAT5A) Is Dependent on Autocrine Activity of Proliferin - Yang, Xinhai (American Society for Biochemistry and Molecular Biology, 2012)
Multiple secreted factors induce the formation of new blood vessels (angiogenesis). The signal transduction events that orchestrate the numerous cellular activities required for angiogenesis remain incompletely understood. We have shown previously that STAT5 plays a pivotal role in angiogenesis induced by FGF2 and FGF8b. To delineate the signaling pathway downstream of STAT5, we expressed constitutively active (CA) or dominant-negative (DN) mutant STAT5A in mouse brain endothelial cells (EC). We found that the conditioned medium from CA-STAT5A but not from dominant-negative STAT5A overexpressing EC is sufficient to induce EC invasion and tube formation, indicating that STAT5A regulates the secretion of autocrine proangiogenic factors. Conversely, CA-STAT5A-induced conditioned medium had no effect on EC proliferation. Using a comparative genome-wide transcription array screen, we identified the prolactin family member proliferin (PLF1 and PLF4) as a candidate autocrine factor. The CA-STAT5A-dependent transcription and secretion of PLF by EC was confirmed by quantitative RT-PCR and Western blotting, respectively. CA-STAT5A binds to the PLF1 promoter region, suggesting a direct transcriptional regulation. Knockdown of PLF expression by shRNA or by blocking of PLF activity with neutralizing antibodies removed the CA-STAT5A-dependent proangiogenic activity from the conditioned medium of EC. Similarly, the ability of concentrated conditioned medium from CA-STAT5A transfected EC to induce angiogenesis in Matrigel plugs in vivo was abolished when PLF was depleted from the medium. These observations demonstrate a FGF/STAT5/PLF signaling cascade in EC and implicate PLF as autocrine regulator of EC invasion and tube formation.